Antibodies against the c-terminus of apoA-1 as predictors of death in the general population but not as therapeutic targets actionable through cognate peptides immunomodulation. (25th November 2020) - Vuilleumier, N; Antiochos, P; Marques Vidal, P; Virzi, J; Pagano, S; Satta, N; Hartley, O; Brandt, K; Burger, F; Montecucco, F; Kutalik, Z; Waeber, G; et al.
Abstract: Aims: Autoantibodies against apolipoprotein A-1 (anti-apoA-1 IgGs) have emerged as an independent biomarker for cardiovascular disease and mortality in humans, promote death in ApoE−/− mice, and seem to be preferentially oriented against the c-terminal part of apoA-1 (cterA1). Corresponding specific mimetic peptides were shown to reverse anti-apoA-1 IgG pro-inflammatory effects in vitro. We evaluated the association of IgG against c-terminus apoA-1 (anti-cterA1 IgGs) with all-cause mortality in the community and tested the ability of two cterA1 mimetic peptides to reverse the anti-apoA-1 IgG-induced inflammation in vitro and mortality in ApoE−/− mice. Methods: Anti-cterA1 IgGs were measured on serum samples of 5220 consecutive participants included in the CoLaus study with median follow-up duration of 5.6 years. The primary study outcome was all-cause mortality. Two chemically engineered optimized cterA1 mimetic peptides were tested i) on HEK cells to modulate interleukin-8 (IL-8) and tumor necrosis-alpha (TNF-α) production, and ii) in apoE−/− mice exposed to 16 weeks of anti-apoA-1 IgG passive immunisation. Results: Anti-cterA1 IgG independently predicted all-cause mortality, each standard deviation of anti-cterA1 IgG being associated with a 18% increase in mortality risk (Hazard Ratio:1.18, 95%confidence intervals:1.04–1.33; p=0.009). Both cterA1 mimetic peptides reduced the anti-apoA-1 IgG-induced inflammation in a dose-dependent manner in vitro, but did not rescue the anti-apoA-1 IgG-associated mortality in mice. Conclusions: Anti-cterA1 IgG independently predict all-cause mortality in the general population. By failing to reverse the anti-apoA-1 IgG-induced mortality in mice, our data do not support the hypothesis that these autoantibodies could be actionable through cognate peptides immunomodulation. Funding Acknowledgement: Type of funding source: Private grant(s) and/or Sponsorship. Main funding source(s): This work was supported by a grant from the Leenaards Foundation (grant number 3698 to N.V.) by the Swiss National Science Foundation (grant number 310030-163335 to N.V.) and by the De Reuter Foundation (grant number 315112 to N.V.).